Penerapan dan Pelatihan Mouse Difabel pada Disabilitas Tunadaksa - Romy Budhi Widodo; Yusuf Giovanno; Yoga Cahyo Utomo; Kevin Christopher Wungow (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2022)
Background: Some physically disabled people cannot operate a computer mouse due to their limitations. But the rest of the arm or thigh can still be moved so that it has the opportunity to be used to move the mouse cursor on the computer screen. The purpose of this activity is to implement a proposed new mouse for physically disabled people, this prototype has reached the technology readiness level (TRL) 6th level. Method: The implementation techniques are as follows: 1) Cloning and repairing the prototypes; 2) Participate in the disablement community; 3) Training disabled persons in Pendopo Lawang Subdistrict, Malang Regency, and getting feedback from subjects and prospective employers of the disabled person. The suggestion of future development of the proposed mouse should be towards spreadsheet processing easily, such as Excel. Results: The prototype was successfully operated, and the basic functions included left-right and top-down cursor movement, and left-click working properly. The feedback from three subjects, two of them successfully used the proposed mouse, while one subject had difficulty. The application of the proposed mouse needs to pay attention to the characteristics of every disabled people. Conclusions: This activity successfully applies the proposed mouse and gets suggestions, as well as prospective employers of the disabled person.